Zimmer : the gender-specific knee - Calkins, Tim; Harmon, Joe (London : Kellogg School of Management, 2007)
Zimmer is the world's leader in artificial knees, with more than a 30 percent market share. At the time of the case, the company was considering investing in a new product, the gender knee. Traditionally, artificial knees were available in a wide range of sizes, but not designed specifically for women and men. Zimmer's research confirmed what orthopaedic surgeons knew--women and men have different knees. However, existing artificial knees worked fine, and there was no evidence that a gender knee would result in improved outcomes for patients. This leads to the question: should Zimmer try to capitalize on its insight about gender knees? Would the upside justify the substantial development cost?
Originally published in Calkins, T., & Harmon, J. (2007). Zimmer: The gender-specific knee. 5-207-252. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Zimmer (Firm); Artificial knee